Ethics at the cinema - Jones, Ward E.; Vice, Samantha, 1973- (New York ; Oxford : Oxford University Press, 2011)
This volume of contributed, previously unpublished essays focuses on general theoretical, meta-ethical and aesthetic issues in philosophy and the ways in which they manifest themselves in film.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Ethics in motion pictures